Technical assistance in the field of risk communication. (29th April 2021) - ,; Maxim, Laura; Mazzocchi, Mario; Van den Broucke, Stephan; Zollo, Fabiana; Robinson, Tobin; Rogers, Claire; Vrbos, Domagoj; Zamariola, Giorgia; Smith, Anthony
Abstract: This report assesses peer‐reviewed and grey literature on risk communication concepts and practices, as requested by the European Commission to support the implementation of a 'General Plan for Risk Communication', i.e. an integrated framework for EU food safety risk assessors and risk managers at Union and national level, as required by the revised EU General Food Law Regulation. We conducted a scoping review of social research studies and official reports in relation to risk communication in the following areas: understanding and awareness of risk analysis roles and tasks, reducing misunderstanding of the different meaning of the terms 'hazard' and 'risk', tackling misinformation and disinformation, enhancing confidence in EU food safety, taking account of risk perceptions, key factors in trade‐offs about risks, audience segmentation and tools, channels and mechanisms for coordinated risk communications. We structured our findings as follows: i) definitions of key concepts, ii) audience analysis and information requirements, iii) risk profiling, models and mechanisms, iv) contributions to communication strategies. We make several recommendations for consideration by the Commission, both in terms of actions to support the design and implementation of the general plan, and research needs that we consider crucial to further inform appropriate risk communication in the EU. EFSA carried out a targeted consultation of experts and a public consultation open to all interested parties including the general public, in preparing and finalising this report. Abstract : This publication is linked to the following EFSA Journal articles: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2021.e190401/full and http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2021.e190402/full